Shock Absorption Characteristics and Optimal Design of Corrugated Fiberboard Using Drop Testing - Chien-Chih Wang; Chin-Hua Chen; Bernard C. Jiang (Applied Sciences, 2021)
The application of corrugated paper to buffer packaging has increased with the rise of the circular economy. The dynamic buffer curve is the key to designing the buffer packaging structure but requires multiple testing by small- and medium-sized enterprises (SMEs) without resources. In this study, we propose drop testing to perform a fractional factorial experiment and establish a regression model of impact strength through experimental data. The analysis results show that static stress, falling height, and buffer material thickness are the key variables of impact strength, and an impact strength prediction model (R2 = 94.1%) was obtained. Model verification using the buffer package design of a personal computer showed that the measured values of impact strength fell within the estimated 95% confidence interval. These results indicate that SMEs can use the proposed analysis procedure to improve the design of corrugated paper using minimal resources.